Financial Performance Analysis and Valuation of a Finalcially distressed New Company in the Indonesian Mining Sector: A Study Case of PT. Cakra Mineral Tbk. - Kramadibrata, Senator; Damayanti, Sylviana Maya (Journal of Business and Management, 2016)
Abstract. Mining sector is the 4th largest economy sector in Indonesia. It contributed to around 16-20% of the country’s GDP and export. In 2009, the government introduced Mining Act law to improve the mining sector and Indonesia’s economy as a whole. Although well-meant, it introduced a myriad of problems in the industry, which impacted the sector as a whole. In addition, falling selling prices, weakening rupiah and lack of infrastructure resulted in decreasing financial performance for mining companies in Indonesia. Enter PT Cakra Mineral Tbk, a new mining company in Indonesia since 2012. It was an agriculture company  specializing in cassava and palm oil before it decided to change its business core to iron ore mining in 2011, based on a feasibility study it conducted since 2010. The company performed terribly for the past years, which is very different compared to the expected performance of its feasibility study. In comparison, many leading mining companies in Indonesia maintained profitability in the last 5 years despite various problems and limitations in Indonesia’s mining industry. As such, this study aims to assess this company’s financial performance and value, compare it with the aforementioned leading mining companies and provide recommendation to be used by its management and investors.The results of this study is that PT Cakra Mineral performed terribly in the last 5 years compared to benchmark companies. In addition, the company generated zero revenue in 2010-2011, rendering DuPont analysis unusable in those years. Market multiples valuation turned out to be inconclusive due to unique circumstances surrounding its stock (CKRA). Discounted cash flow valuation revealed that CKRA is overvalued in base, optimistic and pessimistic scenarios. In conclusion, this study recommends that the company focus more on zircon sands mining, improve mining asset utilization, and acquire more debts if and when the company turned around to become profitable. For investors, it would be wise not to invest in the company at least for the next 5 years, and to stay away from the mining industry in the foreseeable future. Keyword : Financial performance, valuation, discounted cash flow, mining industry.